MENINGKATKAN KETERAMPILAN BERBICARA ANAK MEMALUI PENGGUNAAN CERITA INTERAKTIF DI SPS TSAMROTUL FUAD - Irma Siti Rohimah; Tita Sari (Jurnal Intisabi, 2026)
Early childhoods’ speaking skill need to be developed from an early age because they learn how to communicate with their environment. This study aims to determine the implementation of interactive stories to improve early childhoods’ speaking skill aged 5–6 years at SPS Tsamrotul Fuad. This study used a qualitative research method with a phenomenological approach. The results showed that the implementation of interactive stories was carried out through the stages of apperception, expressive storytelling, involving early childhoods in dialogue and retelling the story. The use of interactive stories has been proven to improve early childhoods’ courage in speaking, enriching vocabulary, and assisting early childhoods to construct sentences more coherently. In conclusion, the interactive story method is well-implemented to improve early childhoods’ speaking skill and can be used as an alternative learning strategy for teachers to develop early childhoods’ expressive language skills.